International relations in the prison of colonial modernity (2017)
This article argues that Justin Rosenberg’s proposal to reground IR in an ontology of societal multiplicity fails to account for the practices by which the field has erased multiplicity from its register and has sustained its identity through suppression of difference. We posit that the prison of colonial modernity, more than that of Political Science, is at the root of IR’s lack of a distinctive purpose, and that Rosenberg’s gesture toward uneven and combined development (UCD) as a sorely needed ‘big idea’ is insufficient for the jail break. © The Author(s) 2017.